Engaging stakeholders in sustainablilty-orientated innovation. - Watson, Rosina (Cranfield University, 2018)
Companies increasingly collaborate with external stakeholders to deliver sustainability- oriented innovations intended to address environmental and social challenges. These partnerships have the potential to combine the diverse resources and capabilities required to implement systemic change, but suffer from conflicts and tensions arising from differences in partners’ objectives driven by their contrasting institutional logics (or ‘value frames’). Through three interconnected studies written as journal articles, this thesis contributes to our understanding of how companies can effectively engage their stakeholders in sustainability-oriented innovation. A systematic literature review integrates evidence from 88 scientific articles into a framework revealing the hierarchy of capabilities required to integrate a company’s stakeholders in sustainability-oriented innovation. Notably, a tier of second-order stakeholder learning capabilities is identified which enables companies to acknowledge, work positively with and learn from differences between themselves and their partners. These differences, as well as the mechanisms and strategies employed to navigate them, are further investigated through eight case studies of sustainability-innovation partnerships. First, findings from a subset of five business-nonprofit partnerships are synthesized into an action-oriented ‘CIMO- logic’ framework which sets out the stakeholder interventions used and the value outcomes generated. Whilst project outcomes are achieved by partners enforcing their own interests through agent control, total value is enhanced when partners recombine their resources and capabilities through resource integration; this process is facilitated by partners navigating differences between their value frames through value empathy. Second, analysis of all eight case studies focuses in on this issue of recognizing and reconciling difference. Five dimensions of difference between partners emerge (goal salience, goal instrumentality, temporal focus, language and collaborative intent) along with five strategies deployed to reconcile tensions arising from these differences (engagement logic alignment, cultural bridging, partner positioning, project scoping and success measurement). Taken together, the thesis’s findings advance our understanding of how companies can effectively integrate stakeholder perspectives into their sustainability-oriented innovation processes. They may have implications for other innovation and partnerships contexts involving stakeholders, including those from diverse institutional settings.
Keywords: Sustainability-orientated innovation; environmental innovation; stakeholder engagement; cross-sector partnerships; dynamic capabilities; institutional logic; systematic literature review; value frames; CIMO-logic; paradox; open innovation